Antitotalitarian pathos in Christoph Ransmayr’s novel «The Last World» in the light of literary anthropology - Давиденко, Іван Олександрович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The present paper studies the antitotalitarian pathos in Christoph Ransmayr’s «The Last World» («Die letzte Welt», 1988). The problem is relatively fresh in literary criticism. The main objective of this paper is to reveal the peculiarities of the characters’ narrative being. In reading Christoph Ransmayr’s novel, the Ovid’s personality arises in recipient’s mind like an old movie. Its scenes remotely resemble the reality. The reason why the writers, the literary critics or just readers become inquiring about the ancient poet is an opportunity to find the answers to the key questions of the human existence in his biography. In addition, even at present no one has the true facts about Ovid’s life. The only proofs we have are the biographical inclusions in his poetry. Therefore the authors have recourse to inexhaustible resources of a myth to fill the numerous gaps in this part of history. The perceptual unity of the poet’s image depends on the reader’s capacity to bring together «the textual puzzles». In the postmodern space of «The Last World» Ovid became the hostage of the absurd world that lives under the law of total control, where fear, inventions, and deformations in social morals dominate. The originality of our scientific solution based on the concepts of literary anthropology. It means that the poetological measurements of the postmodern narrative are not considered separately, but in the context of the fiction being of the main characters and antagonists – the emperor Caesar Augustus and the poet Ovid. Finally the article interprets the conflict between them as an allegory of the voice of free art’s subordination by the totalitarian system.